How efficient is graphene-based nanocomposite to adsorb Hg from seawater: a laboratory assay to assess the toxicological impacts induced by remediated water towards marine bivalves - Coppola, Francesca (2021)
Advanced investigations on the use of graphene based nanomaterials have highlighted the capacity of these materials for wastewater treatment. Research on this topic revealed the efficiency of the nanocomposite synthetized by graphene oxide functionalized with polyethyleneimine (GO-PEI) to adsorb mercury (Hg) from contaminated seawater. However, information on the environmental risks associated with these approaches are still lacking. The focus of this study was to evaluate the effects of Hg in contaminated seawater and seawater remediated by GO-PEI, using the species Ruditapes philippinarum, maintained at two different warming scenarios: control (17 °C) and increased (22 °C) temperatures. The results obtained showed that organisms exposed to non-contaminated and remediated seawaters at control temperature presented similar biological patterns, with no considerable differences expressed in terms of biochemical and histopathological alterations. Moreover, the present findings revealed increased toxicological effects in clams under remediated seawater at 22 °C in comparison to those subjected to the equivalent treatment at 17 °C. These results confirm the capability of GO-PEI to adsorb Hg from water with no noticeable toxic effects, although temperature could alter the responses of mussels to remediated seawater. These materials seem to be a promise eco-friendly approach to remediate wastewater, with low toxicity evidenced by remediated seawater and high regenerative capacity of this nanomaterial, keeping its high removal performance after successive sorption-desorption cycles.